The New Covert Curriculum: A Critical, Actor-Network Approach to Learning Technology Policy - Roberts, George (Proceedings of the International Conference on Networked Learning, 2004)
The overt curriculum of the industrial era, the “3 Rs” was reading, ‘riting and ‘rithmatic. The covert curriculum, inculcated by early modern schooling was punctuality, tolerance of repetition and subordination: compliance with which was important for the functioning of capital intensive industry. Overt curricula are presented as being beneficial for all. Covert curricula benefit particular positions: dominant elites or their powerful oppositional forces. In light of the current consultation on the DfES document, Towards a Unified e-Learning Strategy (DfES 2003), this paper problematises the key affordances of e-learning: flexibility, community and individualisation in order to draw attention to their distopian covert possibilities. Against flexibility might be set a return to piecework and insecurity. Against community and team working might be set normalisation and a re expression of hierarchies. And, against individualisation or personalisation might be set an increased tolerance to surveillance and a willingness to surrender personal information to anonymous, autonomous agents offering only predatory reciprocity.